Operating in cyberspace : a prescriptive model for operating in cyberspace. - Chan, Yong Chao. (2008)
This paper presents an overall architecture of a virtual world in Cyberspace, populated by virtual agents and other similar virtual species. This virtual world will co-exist with the real world, making it imperative for one to have a virtual presence there.